Analgesic effects of Marasmius androsaceus mycelia ethanol extract and possible mechanisms in mice - Jia Song; Xue Wang; Yu Huang; Yidi Qu; Guirong Zhang; Di Wang (Brazilian Journal of Medical and Biological Research, 2018)
Marasmius androsaceus is a medicinal fungus mainly used to treat various forms of pain in China. This study investigated the analgesic effects of an ethanol extract of M. androsaceus (MAE) and its potential molecular mechanisms. Oral administration of MAE (50, 200, and 1000 mg/kg) had significant analgesic effects in an acid-induced writhing test, a formalin test, and a hot-plate test, with effectiveness similar to tramadol (the positive control drug). The autonomic activity test showed that MAE had no harmful effects on the central nervous system in mice. MAE resulted in significantly enhanced levels of noradrenalin and 5-hydroxytryptamine in serum but suppressed both of these neurotransmitters in the hypothalamus after 30 s of hot-plate stimulation. Co-administration with nimodipine (10 mg/kg; a Ca2+ channel blocker) strongly enhanced the analgesic effect in the hot-plate test compared to MAE alone. Moreover, MAE down-regulated the expression of calmodulin-dependent protein kinase II (CaMKII) in the hypothalamus after a 30-s thermal stimulus. These results suggested that the analgesic ability of MAE is related to the regulation of metabolism by monoamine neurotransmitters and Ca2+/CaMKII-mediated signaling, which can potentially aid the development of peripheral neuropathic pain treatments obtained from M. androsaceus.